Synthesis, Characterization and Biological Evaluation of Some 1,3,5-Trisubstituted-2-pyrazolines - ISHWAR BHAT, K.; UMESH KUMAR P., DOBARIYA (Asian Journal of Chemistry, 2010)
A new series of 1,3,5- trisubstituted pyrazolines (7a-j) were synthesized by the condensation of various substituted chalcones (6) with substituted aniline acetyl hydrazides (3) derived from various disubstituted anilines (1) and characterized by IR, 1H NMR and Mass spectroscopic analysis. The compounds were evaluated for antimicrobial activities.